Transformational Leadership Model to Enhance Work Ethic Among Jumantik Cadres in Setu Village : A Community Service Initiative - Didin Hikmah Perkasa; Iyus Wiadi; Lingga Yuliana; Ahmad Azmy; Agung Surya Dwianto; Nur Vitriani (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Through seminars and leadership training, the goal of this community service project is to identify an effective leadership model that will enhance the work ethic of Jumantik employees in Setu Village, East Jakarta. Participating in the Effective Leadership program in enhancing work ethics were 100 Jumantik cadres from the village, the heads of the Development of Family Welfare of Setu Village, Cipayung District, and RW in the Setu Village neighborhood of East Jakarta. Lecture and coaching techniques are used in the training process. As a result of this training, a leader must employ effective leadership techniques to enhance work ethic when overseeing Jumantik cadres. To improve the motivation, accountability, and discipline of Jumantik cadres, one successful leadership model employs a transformational and participatory leadership style. This approach encourages open communication and fosters a sense of belonging among the cadres. It has been demonstrated that cadres who regularly monitor mosquito larvae perform better under leadership that offers clear guidance, emotional support, and active involvement in decision-making. Furthermore, the training emphasizes the importance of collaboration and teamwork, which are essential for achieving common goals. Jumantik cadre supervisors are advised to participate in leadership training since effective leadership would facilitate the development of a more inclusive and cooperative leadership model. Thus, it is anticipated that the effective sub-district eradication of Dengue Hemorrhagic Fever (DHF) will be facilitated by the adoption of the appropriate leadership paradigm, ultimately leading to healthier communities and improved public health outcomes. This is expected to make the public more vigilant and protected from potential online fraud in the future. Furthermore, increased legal literacy is expected to create a safer and more trustworthy digital transaction ecosystem for all parties.